2021
DOI: 10.3390/jcm10225394
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Correlation between Multiparametric Assessment in Ultrasound and Intrinsic Subtype of Breast Cancer?

Abstract: Molecular profile of breast cancer provides information about its biological activity, prognosis and treatment strategies. The purpose of our study was to investigate the correlation between ultrasound features and molecular subtypes of breast cancer. From June 2019 to December 2019, 86 patients (median age 57 years; range 32–88) with 102 breast cancer tumors were included in the study. The molecular subtypes were classified into five types: luminal A (LA), luminal B without HER2 overexpression (LB HER2−), lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Because IHC-based subtyping plays a central role in the management of breast cancer, several studies have been focused on investigating the utility of imaging findings to predict histopathologic prognostic factors. Various studies have shown that US features differ according to prognostic markers and these findings help us to gain a deeper understanding of tumor biology 13,14 . However, inconsistent results obtained from studies and the subjective nature of the US make it harder to generalize the findings and implement routine practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because IHC-based subtyping plays a central role in the management of breast cancer, several studies have been focused on investigating the utility of imaging findings to predict histopathologic prognostic factors. Various studies have shown that US features differ according to prognostic markers and these findings help us to gain a deeper understanding of tumor biology 13,14 . However, inconsistent results obtained from studies and the subjective nature of the US make it harder to generalize the findings and implement routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that US features differ according to prognostic markers and these findings help us to gain a deeper understanding of tumor biology. 13,14 However, inconsistent results obtained from studies and the subjective nature of the US make it harder to generalize the findings and implement routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that compared with other molecular subtypes, triple-negative breast cancers often have relatively clear margins, elliptical shapes, micro lobulated margins, posterior acoustic enhancement and similarities to benign masses such as fibroadenomas. [26][27][28] This may be related to its relatively rapid progression. In addition, we found that Demetics erroneously identified some extremely low echo nodules as anechoic, resulting in misdiagnosis as breast cysts.…”
Section: Characteristic Totalmentioning
confidence: 99%
“…Ultrasound is one of the routine preoperative examinations for breast cancer and has been widely used for the preoperative characterization of breast lesions because it is non-invasive and easy to perform. The molecular staging of breast cancer has been shown to correlate with its ultrasound characteristics (20)(21)(22). Radiomics has been widely used in the diagnosis of breast cancer (23).…”
Section: Introductionmentioning
confidence: 99%